Initial Steps in Developing Critical Thinking by Teaching Philosophy: Scandalon and Rationalization - Nikolić, Ivan Č. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper discusses creating and maintaining certain predispositions for the development of critical thinking as one of the key goals in teaching philosophy. By starting with definitions and recommendations of the Serbian Ministry of Education, Science, and Technological Development related to the goals of teaching philosophy, in this paper we provide a few suggestions for reaching these goals more effectively. We propose a general structural framework from which their realization can be accessed, with scandalon and rationalization as its first two elements. From that perspective, we stress the significance of plasticity and immaturity, as well as some ways to engage them in students. The paper also includes some specific aspects of critical thinking from the viewpoint of logical and methodological literacy. In order to better understand our point, the theoretical framework is backed with a few examples from the classroom. In the conclusion, we point out that these are only the beginning steps in developing critical thinking and that steps like testing and checking are also necessary for fully reaching this goal.